S16.2 Potential for uptake of diagnostic testing services along the continuum of care: landscape assessment of community and providers. (13th September 2015) - Khan, Sadaf; Steele, Matt; Atuyambe, Lynn; Waiswa, Peter; Ali, Nabeel Ashraf; Faulx, Dunia; Arifeen, Shamsul
Abstract : Introduction: Maternal infections continue to be a major contributor to maternal, perinatal, and neonatal morbidity and mortality. The use of diagnostic technologies for maternal infections in the developing world is poorly researched. The current study aimed to elucidate the provider- and patient-level factors that may act to inhibit or encourage timely and effective provision of diagnostic technologies during the pregnancy, intrapartum, and early postpartum periods for infections linked with poor outcomes for mothers and infants in the developing world. Methodology: This was an exploratory study that employed a socio-ecological framework. Using qualitative data collection methods, including focus group discussions (FGDs) with pregnant women, new mothers and their families, and in-depth interviews (IDIs) with lower-level providers, we examined health-seeking behaviours and perceptions of diagnostic testing during pregnancy with the aim of obtaining an in-depth understanding of factors related to the potential for uptake of new diagnostic technologies in two developing country settings (Bangladesh and Uganda). Results: Diagnostic testing during ANC was generally viewed positively. Findings suggest that women and their families would prefer any proposed diagnostic tests be administered by skilled and trained providers. Communities expressed reservations in providing biological specimens during labour and the immediate postpartum period with discomfort and pain during labour and postpartum confinement cited as reasons for these preferences. Blood and urine were deemed the most acceptable specimens, and vaginal swabs were generally not viewed favourably. While providers were familiar with the concept of diagnostic testing, there is limited use of diagnostics in maternal health care, with HIV testing in Uganda being a notable exception. While providers saw definite advantages of diagnostic testing in terms of patient management, they also expressed reservations about the additional work load this would necessitate. Conclusions: There are high levels of receptivity for diagnostic testing among providers and communities with certain caveats regarding specimens and timing.